EVALUASI KEPATUHAN PENGGUNAAN OBAT ANTITUBERKULOSIS (OAT) PADA PASIEN TUBERKULOSIS - Sitta Hasanatin Sholihah (Yayasan Nusantara Hasana Berdikari, 2025)
Pulmonary tuberculosis is a contagious disease caused by the bacterium Mycobacterium tuberculosis that can develop into a chronic disease. Tuberculosis patients who adhere to and regularly take their medication can reduce the risk of therapy failure by 3,76 times compared to tuberculosis patients who do not take their medication regularly. The goal of anti-tuberculosis drug (ATD) therapy is to cure patients, improve productivity, enhance quality of life, and prevent mortality. The occurence of tuberculosis recurrence can reduce the risk of transmission and drug resistance. The method used in this study was an analytical survey with a cross-sectional design. The research data collected were from August 2022 to May 2023. The population in this study were tuberculosis patients at the Rejosari Community Health Center Kudus who were taking anti-tuberculosis drugs (ATD). The sample in this study used the entire population (total sampling), namely 30 patients. The independent variable in this study was knowledge and the dependent variable was medication adherence. The data collection technique used a questionnaire method. The data collected consisted of primary data (data obtained directly from tuberculosis patients, including their knowledge and adherence to anti-tuberculosis medication) and secondary data (medical records and patient medical cards). The data was then computerized through collection, review, and processing. Data analysis was performed using Microsoft Excel with the aid of the frequency distribution table described below. The age characteristics in this study were 3 respondents aged 0-11 years (10.0%), 3 respondents aged 17-25 years (10.0%), 3 respondents aged 26-35 years (10.0%), 6 respondents aged 36-45 years (20.0%), 9 respondents aged 46-55 years (30.0%), and 6 respondents aged 56-65 years (20.0%). The gender characteristics of men were more likely to suffer from pulmonary tuberculosis, namely 17 people (56.7%) compared to the female gender category, namely 13 people (43.3%). Characteristics based on good knowledge were 19 people (63.3%), sufficient knowledge were 6 people (20.0%), and insufficient knowledge were 5 people (16.7%). Characteristics based on adherence to taking OAT were 28 people (93.3%) who were compliant with taking medication and 2 people (6.7%) who were not compliant with taking medication. It can be concluded that of the 30 respondents who were compliant with taking medication, 28 people (93.3%) were compliant with taking medication and only 2 people (6.7%) were non-compliant with taking medication.